Impact of Super Absorbent Polymer and Polyacrylamide on Water Holding Capacity on Ultisol, Lampung - Priyo Cahyono; Akhmad Syaifudin; Afandi Afandi; Winih sekaringtyas Ramadhani (UNIVERSITY OF LAMPUNG, 2024)
Methods of soil and water conservation in tropical wetlands have been carried out is using chemicals to increase the stability of soil aggregates and water-holding capacity. The experiment aims to improve soil stability using Polyacrylamide (PAM) and Super Absorbent Polymer (SAP) materials. Experiment was carried out in R&D Dept. PT. Great Giant Pineapple (PT. GGP), Lampung. The treatment was to mix ingredients into the water with variations the ratio of ingredients (g): water (ml), among others, 1:100, 1:200, 1:300, and 1:400. Next, the SAP/PAM material is mixed into 100 g of soil with a dose of 0 g, 4 g, 8.5 g and 10 g of SAP. After the soil was mixed with the SAP, take as much as 15 g and place it in a pot containing 1 kg of soil. Results experiment show the SAP is a polymer capable of increasing water availability in ultisols and sand used in the experiment and can increase the water content by 18% if compared control. Meanwhile, PAM is a more dominant polymer in its function as an aggregate adhesive instead of a water binder. Super Absorbent Polymer (SAP) and Polyacrylamide (PAM) can chemically function as chemicals for soil conservation.